Arvin Farm Labor Camp - Dorothea Lange:::Creator::::::::::::
Arvin Co-op Store and Gasoline Station, at the entrance to Farm Security Administration Arvin Farm Labor Camp ('Weedpatch'). This store was started 12/15/1939 by 60 camp members who each contributed 1 dollar to get it started. Lange's photographs influenced the development of documentary photography and humanized the consequences of the Great Depression.